DISPARITAS DAN PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT - B61109008, SUKO PRAYOGI (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT The research of disparity and the economic growth in West Kalimantan is designed to analyze the spatial and integral disparity in West Kalimantan. Another purpose of this research is to find out the relationship between disparity and economic growth itself, and examine the causing factors between them. By using the Theil Index Method of measurement the population in West Kalimantan is classified into three different groups, which are coastal regency, the rural regency and municipality. The correlation between disparity and economic growth is found by using the correlation analysis method whereas the causing factors of them were described in descriptive way. The result shows that the disparity was decreased during 2000-2012. It is mostly affected by the between group community rather than the within group. It also proves that there is a significant negative correlation between the disparity and the economic growth. Finally, the result explains that the population, human resources, infrastructure and the capital expenditure are the factors that have an effect on the economic and disparity changes in West Kalimantan. Keywords : Disparity, economic growth, theil index